AKTIVITAS ANTIOKSIDAN ES KRIM BUAH MERAH (Antioxidant Activity of Fruit Red Ice Cream) (UPN VETERAN JAWA TIMUR, 2015)
Abstract Ice cream is one type of food preferred by consumers. In general, the ice cream is made from a mixture of dairy products. The addition of red fruit in ice cream was expected to increase the nutritional value of ice cream products, chemical content in the red fruit was an essential nutrient for the body's defenses such as beta-carotene, tocopherol is an antioxidant compound. The addition of CMC in the red fruit ice cream is expected to maintain the stability of the emulsion and improve the softness of the product. This study aims to determine the effect of red fruit and CMC on the characteristics of the physical, chemical and organoleptic red fruit ice cream produced. The research used Completely Randomized Design (CRD) with 2 factors, the first proportions of red juice: milk cow (15:85; 25:75; 35:65). Second factor is the addition of CMC (0.2, 0.3, 0.4%). The Results red fruit ice cream best treatment was obtained from a combination of red fruit: cow's milk (15%: 85%) with a concentration of 0.2% CMC. The ice cream had a characteristic red fruit with antioxidant activity of 55.61%, 6.96% protein content, fat content of 12.35%, the stability of the emulsion 3.06 g, total dissolved solids 37.00